Peranan Bidang Perdagangan Diskopindag Kota Malang Dalam Menjaga Stabilitas Harga Bahan Pokok - Kuncoro, Dimas Adi; Nafisa, Adita (Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Islam Raden Rahmat Malang, 2025)
Inflation control is an important priority for local governments, especially in Malang City, which has quite volatile staple food prices. This study aims to analyze the strategies used by the government through the Cooperative, Industry, and Trade Agency (Diskopindag) together with related institutions in maintaining price stability. The research method used a descriptive qualitative approach with interviews, observations, and documentation studies, while processing interview results includes data transcription, data coding, categorization, data interpretation and data presentation. The results show that inflation control is carried out through several measures, including the use of the SISKAPERBAPO and SP2KP systems for daily price monitoring, intervention in the distribution of goods to maintain the Maximum Retail Price (HET), education for traders through the SEPASAR PEDAS program, and the implementation of Warung Tekan Inflasi (WTI), which provides basic commodities at affordable prices. This strategy has proven effective in maintaining price stability, increasing transaction integrity, and supporting the creation of a healthy and conducive market.